2014
DOI: 10.1080/03069885.2014.922163
|View full text |Cite
|
Sign up to set email alerts
|

On becoming textually active at Youthline, New Zealand

Abstract: The phones hardly ring at Youthline New Zealand anymore; youth still have problems and seek help, but it mostly happens silently. This article reports on experiences of texting at a 24-hour crisis helpline for young people. To date, there has been no formal evidence base for this practice; however, for new practice, there never is. In prompting discussion, this article attends to the tight constraints that texting imposes, returning to the necessary and sufficient conditions of any effective therapeutic relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 11 publications
3
22
0
Order By: Relevance
“…Questions in both conditions were refined significantly following the initial pilot‐testing. Simple, easy to understand text‐speak was also introduced to the questions, which has been used to increase rapport with young people using text‐message counselling services (Haxell, ). Following further pilot‐testing with a second group ( n = 10) who pilot‐tested the full program with the helpline interface, the final set of questions for both conditions were confirmed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Questions in both conditions were refined significantly following the initial pilot‐testing. Simple, easy to understand text‐speak was also introduced to the questions, which has been used to increase rapport with young people using text‐message counselling services (Haxell, ). Following further pilot‐testing with a second group ( n = 10) who pilot‐tested the full program with the helpline interface, the final set of questions for both conditions were confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…Advantages of text‐message programs with young people include the simple and brief nature of text‐messages, and the private, confidential, and non‐confrontational approach (Perry et al., ; Waller, Franklin, Pagliari, & Greene, ). The ability to store text‐messages allows users to look back over their text‐message history for reference (Haxell, ), and the approach has also been evaluated by youth as a more personal means of health promotion, and the information as more “casual” than if a doctor or teacher was providing it (Gold, Lim, Hellard, Hocking, & Keogh, ).…”
Section: Introductionmentioning
confidence: 99%
“…The texters also reported that the anonymity made it easier to disclose more details about their problems. Haxell (2013) examined text transcripts and interviewed counselors in a New Zealand program. While the service users had a choice between voice and text-based crisis lines, "20% of the helpline user screens would be filled with messages asking, if not demanding, that counselling be provided by text" (p. 149).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have shown positive effects from telephone counselling and chat counselling at child helplines (Fukkink & Hermanns, 2009a;Fukkink & Hermanns, 2009b;King, Bambling, Reid, & Thomas, 2006;King, Nurcombe, Bickman, Hides, & Reid, 2003). While a few articles concern provisions of counselling through SMS technology in the context of child helplines (Gibson & Cartwright, 2014;Haxell, 2015), to the best of our knowledge, no studies have evaluated the impact of different counselling approaches in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to telephone counselling (Rosenfield, 1997), SMS counselling can be accessible, anonymous and efficient (Haxell, 2015). As with all written dialogue, however, SMS counselling offers more time for reflection for both the child and the counsellor than oral dialogue (Fukkink & Hermanns, 2009a;Haxell, 2015;Nieuwboer, Fukkink, & Hermanns, 2014;Sindahl, 2013;Suler, 2000). Like email, SMS is an asynchronous communication technology (Jensen & Helles, 2011).…”
Section: Introductionmentioning
confidence: 99%